If your problem looks like this: 4a-a=_ the answer is... 3a
"a" plus "3a" is equal to 4a. (3a+a=4a). You already have 3 "a's" and then you add another "a."
If 4a+24=72 then you start out by subtracting 24 from both sides because what you do to one side of the equation you must do to the other. That means that 4a+24-24=72-24. So 4a=48. Now you divide both sides by 4 and you get a=12.
a is equal to 1.
4a + 2 = 4(6) + 2 = 24 + 2 = 26
4(a + 6) = 4a + 24
4a + 4b is one possible answer.
5a over 6
It is -44 + 4a
4*4+8 = 24
2a/3=8+4a2a=3(8+4a) 2a=24+12a -10a=24 a=-24/10 a=-12/5
it could be anything. What is a? if it is 3 then you do 4x3=12+3x3=9+3=24 * * * * * It is 8a.
10a + 3a - 4a = 9a
48a3 + 32a2 + 4a = 4a(12a2 + 8a + 1)
5ab-2ab+4a-b+5b = 3ab+4a+4b
a2 - 4a + 4
Add the equations: 4a + 4a - 5b + 5b = 7 + 17 ie 8a = 24 a = 3, so b = 1
It is: 7a+1 when simplified
65 times 4a is equal to 260a.
4a + 3a = (4 + 3)a = 7a
4a4 + 11a3 - 47a3 - 4a + 5 =4a4 - 36a3 - 4a + 5 =4a (a3 - 9a2 - 1) + 5
3a * * * * * Actually, it is 4a.
4a+5=25 4a=25-5 4a=20 a=20/4 a=5
It is an expression of two terms as: 4a+12